Anaerobe‐Inspired Anticancer Nanovesicles. Issue 10 (31st January 2017) - Qian, Chenggen; Feng, Peijian; Yu, Jicheng; Chen, Yulei; Hu, Quanyin; Sun, Wujin; Xiao, Xuanzhong; Hu, Xiuli; Bellotti, Adriano; Shen, Qun‐Dong; Gu, Zhen
Abstract: Anaerobic bacteria, such as Clostridium and Salmonella, can selectively invade and colonize in tumor hypoxic regions (THRs) and deliver therapeutic products to destroy cancer cells. Herein, we present an anaerobe nanovesicle mimic that can not only be activated in THRs but also induce hypoxia in tumors by themselves. Moreover, inspired by the oxygen metabolism of anaerobes, we construct a light‐induced hypoxia‐responsive modality to promote dissociation of vehicles and activation of bioreductive prodrugs simultaneously. In vitro and in vivo experiments indicate that this anaerobe‐inspired nanovesicle can efficiently induce apoptotic cell death and significantly inhibit tumor growth. Our work provides a new strategy for engineering stimuli‐responsive drug delivery systems in a bioinspired and synergistic fashion. Abstract : A biomimetic vesicle mimics the natural mode of tumor targeting and therapeutic drug delivery of anaerobic bacteria. The nanovesicle is stable in cells with normal physiological redox and oxygen balance; however, once disrupted by external light stimuli, it shows dual synergistic anticancer actions with enhanced therapeutic efficacy.